Estimates of energy expenditure and energy consumption of ringed seals (Phoca hispida) throughout the year - Ryg , Morten; Are Øritsland , Nils (Polar Research, 1991)
We have employed a model for the energy balance of seals to estimate the energy consumption and energy expenditure of ringed seals throughout the year, using biological and physical parameters as input. Data on growth and seasonal changes in body mass and fat content “drives” the seasonal dynamics of the model output. The energy requirements for lactation and activity are based on data from earlier published studies. The analysis suggests that the food intake of ringed seals is highly seasonal. In adult males it is low during the periods of territory defense, mating and moulting from March to June. During this period the seals lose body mass, mainly as fat. The model predicts that lactating females increase their food intake to some extent during the approximately six-week lactation period. After the ice breakup, food intake increases in both sexes, partly as a result of increasing maintenance energy requirements, and partly because the body fat stores are rebuilt in late summer and autumn. The over-all energy requirements of the ringed seal appear to be basically similar to those of terrestrial mammals.